PENGUJIAN EFISIENSI PERBANKAN KONVENSIONAL DI INDONESIA MELALUI PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Dara, Siti Ruhana (Economic Faculty, Attahiriyah Islamic University, 2017)
The purpose of this study is to test the efficiency of conventional banking especially Bank Persero, Mix Bank and Bank Pembangunan Daerah (BPD) using a non-parametric analysis of DEA. This research calculates the value of efficiency to the Bank under the category Business Activity (BUKU) as seen from the core capital approach. The sample in this study amounted to 43 banks consisting of 4 Bank Persero, 13 of mix Bank and 26 BPD. The data is published financial statements of banks concerned with the study for 5 years starting from 2008 until 2012. Analysis of the performance efficiency using the Performance Improvement Management Software (PIM-DEAsoft-V3.2) to determine the efficiency of each bank, and then conducted a one-way ANOVA test and two-way to test differences in the average of each category of banks. Bank Persero gain greater efficiency than conventional Bank and BPD and 4th BUKU already doing business more efficient. Keywords: Bank Efficiency, DEA